Volcano tourism in St. Lucia and Dominica: Combining Science and CommunityTT - - Joseph, Erouscilla (Université des Antilles (2015-....), 2019)
Volcanic tourism plays an important role in the economies of the volcanic islands of the Lesser Antilles. On islands like Saint Lucia and Dominica, these volcanoes have been used as geoparks and areas designated as World Heritage Sites. In many of these islands, farming communities also live on the slopes of these volcanoes and, with the increased research of geothermal energy. Volcanic activity therefore has a significant impact on these islands at local and national level. Many volcano monitoring institutions face the financial and human resource challenge of providing continuous monitoring services to economically overburdened small island states. This has often led to the exploration of other low-cost surveillance options and strategies for surveillance agencies, and we present a recent approach using this type of strategy in Saint Lucia and Dominica.